PEMANFAATAN KULIT PISANG KEPOK (Musa paradisiacaLinn) DALAM PEMBUATAN DODOL - Julfan ' '; Noviar ' Harun; Rahmayuni ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this study to get the best formulation dodol with Glutenioos Rice Flour and kepok banana peelsin different ratios, as well as to determine the preference level panelists to dodol produced. This study uses a Completely Randomized Design (CRD) with four treatments and four replications: SN1 (Glutenioos Rice Flour 90% : Kepok Banana Peel 10%), SN2 (Glutenioos Rice Flour 85% : Kepok Banana Peel 15%), SN3 (Glutenioos Rice Flour 80% : Kepok Banana Peel 20%) and SN4 (Glutenioos Rice Flour 75% : Kepok Banana Peel 25%). The results showed that the number of comparisons kepok banana peel and glutnioos rice flour significantly affected the moisture content, ash content, fat content, crude fiber content, sucrose concent, assessment of organoleptic descriptive (color, aroma, flavour and texture) and assessment of organoleptic hedonic overall. The best result of treatment formulation was SN4 (Glutenioos Rice Flour 75% : Kepok Banana Peel 25%) with a moisture content of 16,05%, ash content of 0,50%, fat content 7,85%, crude fiber content 3,09% and sucrose content 46,02%, while the organoleptic assessment results descriptive, dodol generated slightly brown colored, somewhat fragrant flavorful typical banana peel, taste sweet, chewy texture and overall liking ratings for dodol produced is like. Keywords: Dodol, glutenioos rice flour and kepok banana peels.